2006
DOI: 10.1111/j.1472-8206.2006.00432.x
|View full text |Cite
|
Sign up to set email alerts
|

Attenuation of ethanol withdrawal syndrome by extract of Hypericum perforatum in Wistar rats

Abstract: The effects of Hypericum perforatum (St John's wort) on ethanol withdrawal syndrome have been investigated in ethanol-dependent rats. Adult male Wistar rats were subjects. Ethanol (7.2% v/v) was given to rats by a liquid diet for 15 days. Hypericum perforatum extract (HPE) (25-200 mg/kg) and saline were injected to rats intraperitoneally just before ethanol withdrawal. After second, fourth and sixth hour of ethanol withdrawal, rats were observed for 5 min, and withdrawal signs that included locomotor hyperacti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0
1

Year Published

2008
2008
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 48 publications
0
12
0
1
Order By: Relevance
“…HPE (50 and 100 mg/kg) produced positive inhibitory effects on tremor and audiogenic seizures during the withdrawal period in alcohol-preferring rats. These results suggest that HPE could have some beneficial effects on alcohol withdrawal syndrome in people [102]. Hypericum perforatum exhibits remarkable antioxidant potential due to high content of phenolic compounds, especially flavonoids, hyperforin and hypericin [103].…”
Section: Hypericum Perforatummentioning
confidence: 86%
See 1 more Smart Citation
“…HPE (50 and 100 mg/kg) produced positive inhibitory effects on tremor and audiogenic seizures during the withdrawal period in alcohol-preferring rats. These results suggest that HPE could have some beneficial effects on alcohol withdrawal syndrome in people [102]. Hypericum perforatum exhibits remarkable antioxidant potential due to high content of phenolic compounds, especially flavonoids, hyperforin and hypericin [103].…”
Section: Hypericum Perforatummentioning
confidence: 86%
“…Mice Amelioration of liver and brain alcohol injuries through decreasing L-γ-glutamyl transpeptidase and butyryl cholinesterase [76] Humans Decreased signs and symptoms of alcohol hangover [79] Essential oil and citral Mice Hepatoprotective property against AFLD by decreasing levels of D-glucurono-6,3-lactone, glycerol-3-phosphate, and pyruvic acid in serum [80] Opuntia ficus-indica Flavones and phenolics Cladode Humans Reduced hangover symptoms by inflammatory mediator production inhibition [88,89] Rats Suppression of liver damage induced by alcohol through ending free radical chain reactions or enhancing the endogenous antioxidant activities [90] Panax ginseng Ginsenosides Root Humans Relief from hangover symptoms through reduced expiratory and plasma alcohol levels and hangover severity [91] Linoleic acid Mice Alleviation of hangover through reduced alcohol and acetaldehyde levels and enhanced ADH and ALDH activities [92] Mice Suppressed alcohol-induced toxicity on male fertility [93] Ricefish Suppressed alcohol-induced toxicity on embryogenesis [94] Mouse embryos Suppressed alcohol-induced toxicity in the neurocranium through its effects on antioxidant activity [95] Rats Suppressed alcohol-induced toxicity in the gastric system via the restoration of heat-shock proteins [96] Hypericum perforatum Hypericin and hyperforin Leave and flowering tops Rats and mice Reduced voluntary alcohol intake in acute and chronic alcohol treatment through neurochemical mechanisms [101,104,105] Rats Attenuated alcohol withdrawal syndrome by inhibition of the effects on tremors and audiogenic seizures [102] Salvia miltiorrhiza…”
Section: -Gingerol Rhizomementioning
confidence: 99%
“…No entanto, as raízes contêm quantidades mais elevadas desses compostos (Zodi, 2011). Sugerese que as xantonas pertençam a um arsenal químico de defesa empregado pelo HP no combate de fatores de estresse biológico, incluindo as infecções por patógenos e remoção de radicais livres (Crockett et al, 2011). Além das propriedades úteis a planta, as xantonas possuem também utilidades medicinais como anti-inflamatórias, antitumorais, anti-HIV e antimicrobianas (Zodi, 2011).…”
Section: Principais Constituintes Químicos Bioativosunclassified
“…The results suggest that an extract of H. perforatum (HPE) has some beneficial effects on ethanol withdrawal syndrome and that HPE blocks caffeineinduced locomotor hyperactivity in mice. Furthermore, it was reported that HPE may be useful for the treatment of alcoholism in clinical trials (Uzbay et al, 2007;Coskun et al, 2006;Uzbay, 2008).…”
Section: Substance Dependencementioning
confidence: 99%